Polymeric vector-mediated delivery of an miR-21 inhibitor for prostate cancer treatment. Issue 18 (13th February 2017) - Chen, Chuyi; Huang, Xinghua; Wang, Yong; Lin, Liteng; Liu, Lei; Li, Guanyi; Wu, Shangchao; Xu, Chaozhang; Zhou, Jianhua; Shuai, Xintao
Abstract : An miR-21 silencing strategy based on a polymeric vector-mediated delivery system was developed for the effective treatment of human prostate cancer. Abstract : Prostate cancer is one of the most common male malignancies, and MiR-21 plays an important role in the pathogenesis of this cancer. The treatment of microRNAs has proven to be a viable strategy for tumor therapy. However, the delivery of genes remains a major challenge because of the lack of efficient carriers. In this study, a diblock copolymer PEG–PAsp(DETA) of biocompatible polyethylene glycol (PEG) and biodegradable poly(l -aspartic acid) grafted with diethylenetriamine (PAsp(DETA)) was introduced as a delivery vector for an miR-21 inhibitor ( i.e. antisense oligonucleotides for miR-21). Using in vitro and in vivo animal experiments, we studied the transfection efficiency and mechanism of action of the PEG–PAsp(DETA)/miR-21 inhibitor towards prostate cancer PC-3 cells. The biodegradable polymer mPEG–PAsp(DETA) was successfully used as a gene carrier to effectively transport the miR-21 inhibitor into PC-3 cells, which resulted in miR-21 silencing, upregulation of PDCD4 gene expression, and induced apoptosis in PC-3 prostate cancer. Meanwhile, the cytotoxicity of biodegradable carriers is very low. This study demonstrates the potential of our novel nucleic acid nanomedicine for the effective treatment of prostate cancer.